Corruption and legislatures - Pelizzo, Riccardo; Stapenhurst, Frederick (New York : Routledge, 2014)
'This book investigates parliaments' role in curbing corruption. In addition to discussing the definition, causes, and costs of corruption and the role that parliaments have in reducing corruption, the authors consider contemporary issues that parliamentarians - and others - need to be aware of. These include the importance of broad-based coalitions to fight corruption and networking at the country, regional and global level, the importance - and difficulties - of establishing parliamentary codes of ethics/conduct, legislative oversight tools and mechanisms, and regional/international conventions against corruption. Attention will also be given to parliaments and anti-money laundering. Corruption and Legislatures presents a non-technical review of contemporary issues and recent developments in curbing corruption, and concludes with practical advice as to what can be done to ensure more effective parliamentary involvement in curbing corruption'--
Introduction -- The dividends of good governance -- Strategies to curb corruption : the role of the legislature -- The effectiveness of legislative oversight : the case of Ghana and Nigeria in comparative perspective -- Legislative corruption, public trust and political will -- Legislative ethics -- Political finance -- Conclusions.
Includes bibliographical references and index.
Keywords: Legislative oversight; Legislative oversight -- Moral and ethical aspects; Political corruption; Political corruption -- Prevention; Political ethics; Comparative government